Mass fractal characteristics of silica sonogels as determined by small-angle x-ray scattering and nitrogen adsorption - Donatti, D. A. [UNESP]; Vollet, D. R. [UNESP]; Ibañez Ruiz, A. [UNESP]; Mesquita, A. [UNESP]; Silva, T. F.P. [UNESP] (American Physical Society (APS), 2005)
A sample series of silica sonogels was prepared using different water-tetraethoxysilane molar ratio (r w) in the gelation step of the process in order to obtain aerogels with different bulk densities after the supercritical drying. The samples were analyzed by means of small-angle x-ray-scattering (SAXS) and nitrogen-adsorption techniques. Wet sonogels exhibit mass fractal structure with fractal dimension D increasing from ∼2.1 to ̃2.4 and mass-fractal correlation length ξ diminishing from ∼13 nm to ∼2 nm, as r w is changed in the nominal range from 66 to 6. The process of obtaining aerogels from sonogels and heat treatment at 500 °C, in general, increases the mass-fractal dimension D, diminishes the characteristic length ξ of the fractal structure, and shortens the fractal range at the micropore side for the formation of a secondary structured particle, apparently evolved from the original wet structure at a high resolution level. The overall mass-fractal dimension D of aerogels was evaluated as ∼2.4 and ∼2.5, as determined from SAXS and from pore-size distribution by nitrogen adsorption, respectively. The fine structure of the secondary particle developed in the obtaining of aerogels could be described as a surface-mass fractal, with the correlated surface and mass-fractal dimensions decreasing from ∼2.4 to ∼2.0 and from ∼2.7 to ∼2.5, respectively, as the aerogel bulk density increases from 0.25 (r w = 66) up to 0.91 g/cm 3 (r w = 6). © 2005 The American Physical Society.